Design of Freezing Bed for Sludge Dewatering at McMurdo, Antarctica - Martel, C. J. (2001)
This report contains a design analysis for a freezing bed for sewage sludge at McMurdo Station, Antarctica. This analysis indicates that all the sludge produced by the proposed wastewater treatment plant at McMurdo could be dewatered in a 10-by 16-m by 2-m-deep freezing bed. Sludge would be frozen by pumping it into the bed in 8-to 10-cm layers during the months of March through September. The total depth of frozen sludge by the end of this period is estimated to be 1.5 m. This sludge would be thawed and drained during the austral summer months of October through January. The sludge would be removed and the bed would be reconditioned during February. The sludge would be thawed with solar radiation and waste heat from the effluent. Installation of the freezing bed would reduce operation and maintenance costs by 98% compared to a conventional belt press.